MO315: Risk Factors for CSA-AKI and Performance of Leicester Score in a Spanish Cohort. (3rd May 2022) - Molina Andujar, Alicia; Joaquin Escudero, Victor; Blasco, Miquel; Piñeiro, Gaston; Poch, Esteban
Abstract: BACKGROUND AND AIMS: The incidence of acute kidney injury following cardiac surgery (CSA-AKI) is up to 30% and it places patients at an increased risk of death. Leicester score (LS) is a new score designed by Birnie et al. [1 ] and validated in 2014 in a British Cohort. It predicts CSA-AKI at any stage with better discrimination compared with the Clevaland Clinic Score (CCS) and Euroscore II. The aim of this study was to identify risk factors for CSA-AKI and to assess the performance of LS in a Spanish cohort. METHOD: A unicentric retrospective study of patients that required cardiac surgery with cardio-pulmonary bypass (CPB) during 2015 in the Hospital Clinic de Barcelona. The inclusion criteria were patients >18 years old who were operated on for cardiac surgery [valve substitution (VS), coronary artery bypass graft (CABG) or a combination of both procedures] with the need of CPB. CSA-AKI was defined by the Kidney Disease Improving Global Outcomes (KDIGO) criteria. RESULTS: A total of 444 patients were included, of which 171 (38.5%) developed CSA-AKI. The most frequent form of AKI was mild AKI (AKI stage 1), which was present in 105 patients (61.4%). AKI stage 3 was developed in 26 patients, 15 of which required RRT. A total of 66.7% of AKI cases met criteria in the first 24 h and the median duration until total recovery was 3 days. In the multivariate analysis, hypertension (OR 1.883), EGFR < 60 mL/min (OR 2.365) and peripheral vascular disease (OR 4.66) were associated with CSA-AKI. Either discrimination or calibration were better with LS compared with CCS and Euroscore II, with an AUC of 0.721 versus 0.595 and 0.662, respectively (Fig. 1 ). CONCLUSION: Preoperative hypertension in patients with CKD with or without peripheral vasculopathy can identify patients at risk of CSA-AKI. LS has proved to be a valid score that could be used to identify patients at risk who could benefit in intervention studies.